Juegos tradicionales y el pensamiento lógico-matemático en niños de 4 a 5 años de la Unidad Educativa José Ángel Palacio de la ciudad de Loja, periodo 2023-2024 - Barrionuevo Pogo, Andrea Cecibel (2024)
Logical-mathematical thinking is the ability that children have to recognize basic mathematical concepts, such as number-quantity, geometric shapes, and object comparison, highlighting that traditional games are essential for enhancing mathematical skills. This research analyzed the contribution of traditional games to the development of logical-mathematical thinking in children aged 4 to 5 years at José Ángel Palacio Educational Institution in the city of Loja, 2023-2024. A non-experimental research design was used, focusing on data collection and analysis. Additionally, both quantitative and qualitative approaches were employed to describe the characteristics and strategies of the variables, utilizing inductive-deductive and analytical-synthetic methods that facilitated a detailed study and analysis of all information. Observation was used as a technique by applying the Early Mathematical Assessment Test, evaluating mathematical competencies in a sample of twenty-three children. The results showed that 65% of the participants exhibited difficulties at moderate and low levels in the development of logical-mathematical thinking. An alternative proposal called “Adventures with Tradition” was designed, consisting of thirty traditional games, which was provided to the teacher for application with the children. Based on the findings, it was concluded that traditional games are essential for learning, serving as effective methodological strategies that contribute to strengthening mathematical skills. Furthermore, these activities are enjoyable and can be conducted in a free environment, and use easily accessible materials. Keywords: mathematical skills, logical, games, playful, concepts.